Genetic profiling of inherited colorectal cancer syndromes in Tunisian patients - Rania Abdelmaksoud-Dammak; Nihel Ammous-Boukhris; Amena Saadallah-Kallel; Dorra Ben Ayed-Guerfali; Souhir Guidara; Imen Miladi-Abdennadher; Ikhlas Ben Ayed; Hassen Kamoun; Slim Charfi; Tahya Sellami-Boudawara; Imen Zribi; Foued Frikha; et al. (PLoS ONE, 2025)
Objective Colorectal cancer (CRC) is among the most commonly diagnosed cancers worldwide, with 2% to 5% of cases being linked to inherited syndromes. Material and methods A cohort of 30 Tunisian patients was selected and divided into two groups based on clinical features and family history: Group 1 included patients clinically diagnosed with hereditary polyposis syndromes, including MUTYH-Associated Polyposis (MAP: 15 cases) and Familial Adenomatous Polyposis (FAP: 5 cases). Group 2 consisted of patients clinically diagnosed with non-polyposis syndromes, including Lynch Syndrome (LS: 7 cases) and other rare syndromes (OS: 3 cases). Genetic testing was performed using either Sanger sequencing or targeted next-generation sequencing (NGS) with a cancer panel including 31 cancer-related genes. Results In Group 1, MAP was confirmed in 13 patients who were homozygous carriers of the pathogenic variant (c.1143_1144dup p.Glu382fs) in the MUTYH gene. For patients suspected of having FAP, pathogenic variants in the APC gene were identified in only two patients (c.3183_3187del p.Lys1061_Gln1062insTer, and c.2016_2017del p.His672Ter), while another patient carried a frameshift variant (c.502_503del, p.Ile168SerTer11) in the PTEN gene, indicating Cowden Syndrome. In Group 2, genetic testing confirmed Peutz-Jeghers Syndrome in a young girl who had a large deletion in the STK11 gene. For patients suspected to have LS, only variants of unknown significance (VUS) were identified in MMR. Further genetic investigations are required to identify the pathogenic variant in these patients. Conclusion Overall, our results highlight the importance of genetic testing to better understand hereditary CRC syndromes in Tunisian families, and to improve the management of patients and their relatives.